Osteochondritis dissecans of the humeral capitellum in identical twins - Pudas, Tomi (SAGE Publications, 2012)
Osteochondritis dissecans (OCD) of the humeral capitellum is a disorder affecting mainly boys between the ages of 12 and 15 years. The exact etiology of OCD is not clear, but it is believed that repetitive trauma is the primary cause. Genetic factors are thought to play a secondary role in the pathogenesis. We present 17-year-old identical twins with similar MRI and arthroscopic findings, suggesting that genetic components are involved in the etiology of OCD of the humeral capitellum.